Factors Influencing The Incidence Of Stress Fractures Based On The Characteristics of Command Education Students At The Special Forces Command Education And Training Center In Batujajar, West Java, Indonesia: A Retrospective Approach With Secondary Data - claudiva kirana; Dian Andriani Ratna Dewi; Sissy chen; sausan maulida (The ASEAN Journal of Military and Preventive Medicine, 2026)
Stress fractures caused by repetitive mechanical loading represent a significant threat to physical performance and operational readiness among military personnel. This study aimed to identify factors associated with stress fracture occurrence among command education students at the Special Forces Education and Training Center in Batujajar, West Java, Indonesia. A retrospective descriptive study was conducted using secondary data from forty-three documented stress fracture cases collected over a six-year period. The variables analyzed included age, body mass index (BMI), and anatomical location of the fracture. Data were analyzed using univariate and bivariate descriptive analysis to characterize the distribution of stress fractures based on the studied variables. The results showed that the majority of cases occurred in individuals aged 20–25 years (90.7%), with the left tibia being the most frequently affected anatomical site (34.9%). All subjects had BMI values within the normal range, indicating no significant association between abnormal BMI and stress fracture occurrence. These findings suggest that age and fracture location are key characteristics of stress fractures among command education students. The study provides evidence to support the development of targeted prevention and early intervention strategies aimed at reducing stress fracture incidence, improving training completion rates, and enhancing the operational readiness of special forces personnel.